East Africa: Kenya - Agriculture, food security and climate change outlook - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Agriculture is central to Kenya’s economic development, constituting 28% of the country’s GDP and accounting for 65% of total export earnings. The crop, livestock, and fishery sub-sectors contribute approximately 78%, 20%, and 2% to the agricultural GDP, respectively. The sector employs more than 80% of Kenya’s rural workforce and provides about 18% of total formal employment. The country profile shows 98% of Kenya’s crop production is rain-fed, however, only 15% of the country receives sufficient rainfall for crop production with very small landholdings (0.3–3 ha) and extremely limited irrigation (less than 0.16% of arable land). This poses the greatest challenge on development of more resilient food systems in the changing climate.